Effect of Aqueous Extract of Tribulus terrestris orally administration on some Biochemical Parameters in Castrated Male Rabbits: Abeer Uthman Moosa1; Rasha Hussein Kuba7 and Yasser A.H. AL- Issa - Moosa, Abeer Uthman (The Iraqi Journal of Veterinary Medicine, 2012)
The present study is aimed to investigate the influence of an aqueous extract of Tribulus terrestris on some biochemical parameters namely, alkaline phosphatase (ALP), Iron, phosphate (PO4), sodium (Na+), potassium (K+), aldosterone, and cortico steroid in unilateral and bilateral castrated male rabbits. Thirty mature male rabbits which are divided randomly in to six groups. group 1: is control, group2: orally administrated 150 mg / kg / day of an aqueous extract of T. terrestris, group3: is bilateral castrated rabbits received D. W., group4: is bilateral castrated rabbits received (150 mg / kg / day) of the extract, group 5: unilateral castrated rabbits received D. W., group 6 is unilateral castrated rabbits received 150 mg / kg / day of the extract, all doses were given orally every day for 30 days. At the end of the experiment, sera were collected and biochemical tests measured. The results showed a significant (P<0.05) increased in ALP level in group 2 and in PO4 level in group 5 in comparison with group1, while PO4 level tended to be decreased significantly (P<0.05) in group 6 when it compared with group 5. The results also showed a significant(P<0.05) increased in (K+) and (Na+) in group 2 and group 6 in comparison with group1 while there was a significant(P<0.05) decreased in (K+) and (Na+) in group 4 when it compared with group 2. In addition there was a significant (P<0.05) increased in aldosterone concentration in group 6 compared with group 1 and group 2. While there was a significant decreased in cortico steroid concentration in group 3 , 5 and 2 compared with group 1 but the cortico steroid showed a significant (P<0.05) increased in group 6 compared with group 1. There were no significant differences between groups concerning the iron concentration.